Effectiveness of Catering Owners' Knowledge in Early Warning of Food Poisoning Outbreaks in Medan City - Rapida Saragih; Dasman, Hardisman; Indrapriyatna, Ahmad Syafruddin; Yani, Finny Fitry; Lipoeto, Nur Indrawaty; Yetti, Husna; Ilmiawati; Harun, Harnavi (proceedinginternational, 2025)
Food poisoning outbreaks are a serious problem that can have a significant impact on public health. Food poisoning occurs when food consumed is contaminated with bacteria, viruses, parasites, or hazardous chemicals. Medan City experiences fluctuating food poisoning incidents, so continuous monitoring is needed to identify and address the causes. The purpose of this study was to determine early warning by using a module to prevent food poisoning outbreaks. This study was conducted quantitatively using an experimental design with the one group pretest-posttest design (before and after) approach. The location of the study was carried out at the Medan City Health Office and a population of 20 respondents, while the sample, namely the total population, was the sample. The data obtained were analyzed univariately, bivariately. The results showed that knowledge in catering owners with n = 20, paired sample T-test there was a significant difference between the level of knowledge of respondents about food poisoning before and after the intervention using the module p value = 0.0001 (<0.05). The module that has been developed and validated by language experts with results of 94.3, material experts with 97.3 and media experts with 91.3 can effectively prevent poisoning. It is recommended to the local Health Service and Health Center to be able to use the module as an early warning model for food poisoning outbreaks, especially for catering business owners, so that they can increase knowledge, especially in carrying out prevention. Keywords: Knowledge, Early Warning, Outbreak, Food Poisoning.